Gambaran Higiene Sanitasi Pengelolaan Makanan di Rumah Sakit ABC Kabupaten Kubu Raya Kalimantan Barat - Faradila Sintia; Susilawati Susilawati; Fathmawati Fathmawati (Jurnal Sehat Mandiri, 2020)
Hospital is a health service institution that conducts complete individual health services, which include inpatient, outpatient, and emergency services. Hospitals should minimize the source of diseases caused by food, especially for patients who are hospitalized, therefore hospitals must meet the hygiene requirements for food management. This study aims to describe the implementation of food management sanitation hygiene at ABC Hospital Kubu Raya Regency. This was a descriptive study by observing the components of food management sanitation hygiene at ABC Hospital. Data were collected using a checklist. The analysis was done by comparing the results obtained with the assessment component based on the some Minister of Health regulations. The results of this study indicate that some components of food management must be improved in order to ensure the safety and health of users. Further research needs to develop an instrument for assessing food-management sanitation hygiene in a hospital.